H-BRIDGE THIRTEEN LEVEL INVERTER USING REDUCED NUMBER OF SWITCHES FOR INDUSTRIAL APPLICATIONS - S.Vijayabaskar; D.Subramani; K.Manoj; P.Vishnuprasanth, (EPRA International Journal of Research and Development (IJRD), 2022)
The single phase cascaded H-bridge multilevel inverter (Thirteen level) is designed for industrial applications and has a decreased number of switches. Cascaded Multilevel Inverters are widely used in the electric utility industry and for industrial motors. When these inverters are used directly for industrial drives, the THD contents in the output voltage of the inverters are extremely important since the performance of the drive is highly dependent on the quality of the voltage applied to it. The symmetric and asymmetric inverters are two forms of cascaded H-bridge inverters that use input voltage from various sources. Only one H-bridge (with four switches) and three additional switches make up the proposed asymmetric cascaded H-bridge topology, which has a total of seven switches for a 13-level output voltage. Drives and renewable energy applications benefit from the new topology. For different layers of multilevel inverters, THD is determined by modulation index. The THD is decreased to 9.18% using the PWM approach, and the THD is analysed using MATLAB/SIMULINK. The proposed topology has been tested utilising a single phase 13 level inverter and a DSPIC 30F2010 controller.